Sanksi Pidana Penyalahgunaan Pengangkutan Bahan Bakar Bersubsidi - I Dewa Gede Sastra Buwana; I Wayan Rideng; I Ketut Sukadana (Warmadewa Press, 2020)
Oil and gas is a natural resource controlled by the state and is a source of vital commodities that play an important role in every human activity. The misuse of the transportation and trade of fuel subsidized by the government by certain individuals can take away the rights of the less fortunate and result in losses to the state. This research explains how to arrange the transportation or commercialization of subsidized fuel and to find out the criminal sanctions for the perpetrators of misuse of subsidized fuel. The research method used is Normative Law research. The statutory approach to the problem is to analyze from the point of view of statutory regulations and relevant theories. Sources of legal materials in this study are primary and secondary legal materials. The technique of collecting legal materials is obtained from legal literature materials by collecting, reading and recording legal materials related to the crime of misuse of subsidized fuels. The results of this study are first, the regulation of legal protection and supervision has been regulated in accordance with the provisions of Article 46 of Law No. 22 of 2001 on Oil and Gas. Second, legal sanctions against perpetrators of misuse of subsidized fuel: case at the Gianyar District Court (PN) case number 153 / Pid.Sus / 2017 / PN. Gin is cumulative in nature, as regulated in Article 55 of the Republic of Indonesia Law No. 22 of 2001, namely given a verdict in the form of a prison sentence of 10 (ten) months and a fine of 2 million rupiahs provided that if the fine is not paid, it is replaced by imprisonment for 2 (two) month